"We Need to Talk About Empathy": Dutch Humanist Chaplains' Perspectives on Empathy's Functions, Downsides, and Limitations in Chaplaincy Care. (March 2022) - van Dijke, Jolanda; Duyndam, Joachim; van Nistelrooij, Inge; Bos, Pien
This paper investigates the functions, downsides, and limitations of empathy in chaplaincy care. Data were collected from 20 humanist chaplains working in health care, prison, and military settings using semi-structured interviews. According to the participants, empathy is at the heart of their profession but has disadvantages as well. The analysis yields seven major functions of empathy with corresponding downsides and limitations: (1) to connect, (2) to understand, (3) to guide, (4) to acknowledge, (5) to motivate, (6) to inspire, and (7) to humanize. We argue for a need to "talk about empathy" since despite its importance and challenges, there is little professional and academic discussion about empathy in chaplaincy care. We hope that the findings of this study can function as starting points for the discussion and thus contribute to the ongoing professionalization of chaplaincy care. To that end, we propose three topics for further reflection and conversation.